2006
DOI: 10.1590/s0004-282x2006000600019
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do tratamento neonatal com inibidor seletivo de recaptura da 5-HT sobre o desenvolvimento anatômico crânio-encefálico

Abstract: RESUMO -Pesquisadas re p e rcussões neonatais do tratamento crônico com inibidores seletivos de re c a p t u r a da serotonina (ISRS) sobre crescimento somático, do encéfalo e crânio. Ratos machos foram divididos em g rupos: controle (NaCl) e Cit (10 µL/Kg citalopram 10 mg). Durante 21 dias pós-natais, foram aferidos peso corporal, eixo látero-lateral, ântero-posterior e circunferência do crânio. Aos 8, 15 e 22 dias pós-natais, os animais foram sacrificados para retirada do encéfalo para avaliar as medidas cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In agreement with our study, Silva et al (Silva et al 2010) and da ), using the same experimental model that we apply in our study, demonstrates that chronic fluoxetine treatment induced less weight gain and less body weight since lactation and maintain in adult life. Another study using the antidepressant citalopram (10 mg / kg bw, sc) also demonstrated reduced body weight (Magalhaes et al 2006). The antidepressant fenfluramine (reuptake inhibitor and 5-HT release stimulator) increased proopiomelanocortin (POMC) expression (Heisler et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…In agreement with our study, Silva et al (Silva et al 2010) and da ), using the same experimental model that we apply in our study, demonstrates that chronic fluoxetine treatment induced less weight gain and less body weight since lactation and maintain in adult life. Another study using the antidepressant citalopram (10 mg / kg bw, sc) also demonstrated reduced body weight (Magalhaes et al 2006). The antidepressant fenfluramine (reuptake inhibitor and 5-HT release stimulator) increased proopiomelanocortin (POMC) expression (Heisler et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Other studies evaluated the somatic development in Wistar rat in particular the ones of our laboratory LAFINT (Deiró;Barros;Magalhães, 2000;Freitas-Silva, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…• Brain development indicators: Post mortem evaluations were performed on animals at 8, 15 and 21 days of age. After craniotomy, the brain was removed from the cranial box, and the following measurements were performed: weight, volume, diameter and circumference of the encephalon, cerebellar weight, anterior-posterior encephalic axis (APEA), anterior-posterior cerebellum axis (APCA), anterior-posterior brain axis (APBA), laterolateral axis of the brain (LLBA), and laterolateral axis of the cerebellum (LLCA) (Magalhães et al 2006).…”
Section: Parameters Analyzedmentioning
confidence: 99%